ENGARUH SISTEM PEMASARAN KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING DAN INOVASI PADA UKM KULINER KOTA MEDAN - Marissa Claudya; Wan Suryani; Tohap Parulian (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This research is motivated by the importance of marketing strategies marketing activities in small and medium-sized businesses to survive in competition between businesses. Researchers want to find out how the influence of the entrepreneurial marketing system that is focused on small and medium enterprises on the formation of innovation and competitive advantage where entrepreneurial marketing plays a role in innovation as well as entrepreneurial marketing on competitive advantage and innovation has a role that affects competitive advantage. The study was conducted on culinary UKM in the city of Medan. This type of research is a survey method with explanatory research. The sample of this study was 80 respondents with a random sampling technique. The analytical method uses PLS-3 (Partial Least Square). The results of this study indicate the first hypothesi there is a significant and positive effect between entrepreneurial marketing and innovation. The second variable hypothesis is entrepreneurship marketing with competitive advantage. The third hypothesis between innovation and competitive advantage.